Robust Control with Dynamic Compensation for Human-Wheelchair System - Andaluz, Victor (2014)
This work presents the kinematic and dynamic modeling of a human-wheelchair system, and dynamic control to solve the path following problem. First it is proposed a dynamic modeling of the human-wheelchair system where it is considered that its mass center is not located at the center the wheels’ axle of the wheelchair. Then, the design of the control algorithm is presented. This controller design is based on two cascaded subsystems: a kinematic controller with command saturation, and a dynamic controller that compensates the dynamics of the robot. Stability and robustness are proved by using Lyapunov’s method. Experimental results show a good performance of the proposed controller as proved by the theoretical design.